Results 1 to 1 of 1

- Jun 25th 2008, 09:03 AM #1

- Joined
- Jun 2008
- Posts
- 4

## N(t) = γA(t-τ)

A step forward from N(t) = γA(t) situation.

N(t) = γA(t-τ)

As before, N(t) is a known number (of peatlands) at time t, A(t) is a known area (deglaciated) at time t. γ is a hypothethical number of peatlands that can form per unit of deglaciated area.

τ is a delay period (before peatlands get established).

Ok, so I got y solved. I'm not quite sure though if I should use the variable y for each time or the average value for all. I tried both. Neither makes any sense with the following

> A(t-τ) = N(t)/y

> A(t)-A(τ) = N(t)/y

> A(τ) = A(t) - N(t)/y

Is this correct so far? Probably not, because it doesn't give any meaningful answer. And I don't know what A(τ) actually is, what I want to find is τ.